Peacemaking - what's law got to do with it, 2015-2019 - Nouwen, Sarah M. H. (UK Data Service, 2021)
Studying various aspects of the relationship between peacemaking and international law, this project used a wide range of data. For the first aspect, which was to examine assumptions underpinning claims about the contribution of international legal mechanisms towards peacemaking, it looked at official documents, press statements, promotional material and academic literature on the International Criminal Tribunal for the former Yugoslavia (ICTY), the International Criminal Tribunal for Rwanda (ICTR), the International Criminal Court and that of international commissions of inquiry. It then relied on earlier empirical research, by other researchers and this researcher, to consider the assumptions in light of the empirical evidence. For the second part of the research, which examined the conceptualisation of the relationship between peace and justice in the context of the international law on self-determination, the project obtained thousands of photographs of relevant material in the Sudan Archive at Durham and the National Archives at Kew. For the more contemporary aspect of the study, it collaborated with area experts. For the third aspect of the project, namely shedding light on changing meanings of peace, it collaborated with a team of Sudan and South Sudan experts, to produce a multiperspectival approach on understandings of peace and peacemaking. Moral philosophers and international lawyers have been working on identifying and developing 'norms' that govern the transition from conflict to peace generally and peace negotiations particularly. It has been argued, for instance, that international law prohibits amnesties for international crimes, forbids engaging people accused of such crimes in peace talks, and outlaws certain power-sharing agreements. Vice versa, it has been suggested that international law determines that some groups must participate in peace talks, that issues such as gender equality must be regulated by a peace agreement and that topics such as human rights violations must be raised in peace talks. These putative 'norms' can have a decisive impact on peace talks: parties may not want to talk peace if they are threatened with prosecution or if they cannot obtain a power-sharing arrangement. Focus on gender and human rights, in turn, may contribute to a blueprint for an ideal state, but turn attention away from issues that are dividing the parties. In response to demands from practice, this project aims to clarify the role of international law in peace negotiations in 3 ways. First, it assesses whether the 'norms' suggested by the literature in fact amount to international law. Most of the proposed norms are based on moral philosophy or a review of practice. But these are not sources of international law. This project is the first to examine through an interpretive empirical study whether the putative norms find support in the sources of international law. This will not only advance the discipline of international law, but also assist practising negotiators. Secondly, this project aims to clarify the existing scholarship on the 'law' of peacemaking by developing a taxonomy of the various concepts of 'law' that are currently used in this body of literature. This clarity is also important to practising negotiators. If the 'law' of peacemaking is 'law' in the sense of 'model law', then it can be ignored at will. Ignoring binding 'international law', however, can lead to international responsibility. Finally, evaluating the empirical findings, the project will explore what drives attempts to govern peacemaking by more international law. In doing so, it will contribute to a literature on possible changes in the sources of international law and to scholarship on the more general phenomenon of legalisation in society. It will also assist those who make international law in the evaluation of proposals towards further legalisation. Matching the interdisciplinarity of the project, each of the research objectives will be pursued with a methodology and method that fits the type of question involved. The data-gathering methods will include interviews with key actors in peace negotiations, at headquarters of international organisations (United Nations and African Union) and in situ in three case studies (Sudan, Somalia and Uganda). Practitioners, including from the UN and AU, have been consulted in the development of this proposal; will influence the implementation through their role in interviews, the Advisory Group and the Nexus (a week-long mutual knowledge transfer between academics and practitioners) and will be involved in the dissemination. This will guarantee the highest degree of impact. In sum, this project can make a fundamental contribution to the future course of proposals on a law of peacemaking; understanding of the interaction between law and peace processes; the literatures on peace and conflict studies and international law; methodologies that integrate normative and empirical research and break boundaries between scholarly and practitioners' knowledge; and, most fundamentally, the increasing practice of peace negotiations. The project will be supported by a bespoke career development programme with cross-disciplinary mentoring from peace and conflict studies and international law, a study visit and several training courses.